A microalga, Euglena tuba induces apoptosis and suppresses metastasis in human lung and breast carcinoma cells through ROS-mediated regulation of MAPKs. Issue 1 (December 2016) - Panja, Sourav; Ghate, Nikhil; Mandal, Nripendranath
Abstract Background Euglena tuba, a microalga, is known for its excellent antioxidant and iron-chelation activities; however its anticancer efficacies have not been reported yet. This study investigates the antitumor and antimetastatic activities of 70 % methanolic extract ofEuglena tuba (ETME) against human lung (A549) and breast cancer (MCF-7) cells in vitro. Moreover, we had examined ETME's role in inducing intracellular ROS with the regulation of antioxidants and MAPK pathway. Methods Anticancer activity of ETME was thoroughly studied using flow cytometry, confocal microscopy and western blotting; along with various biochemical assays for analysing ROS-induced regulation of antioxidant enzymes. Inhibition of invasion and migration of malignant cells by ETME were investigated by wound healing and zymographic studies. DNA–Protein interaction with ETME was also studied. Results ETME inhibited the growth of both A549 (IC50 92.14 µg/ml) and MCF-7 cells (IC50 50.27 µg/ml) by inducing apoptosis, while remained non-toxic against nomral WI-38 cells (IC50 911.43 µg/ml). ETME treatment resulted in increasing Bax/Bcl-2 ratio, BID truncation and activation of caspase cascade. This ultimately leads to PARP degradation and apoptosis through the intrinsic and extrinsic pathway in both A549 and MCF-7 cells. Wound healing and gelatin zymography studies revealed that ETME significantly inhibited the invasion and migration of both A549 and MCF-7 cells dose-dependently through the downregulation of MMP-9. Further investigations showed that ETME selectively induces intracellular ROS, regulated the levels of intracellular antioxidants and suppresses the activation of ERK1/2, JNK, P38 mitogen-activated protein kinase pathways in both type of malignant cells. Further DNA and protein binding studies revealed that ETME strongly interact with DNA as well as protein attributing the possibilities of presence of components which are targeting the macromolecules in cancer cells. Moreover, when the identified compounds from ETME were examined for their cytotoxicities individually, it was found that they lost their specificities towards cancer cells and also attacked normal cells. Conclusions Our study suggests that ETME retards the growth of both lung and breast cancer cells, in vitro, through multivariate mechanisms, proving its candidature for the development of better and safer drugs against these cancers.